Clinical Study of Electro-acupuncture Treatment with Different Intensities for Functional Constipation Patients - 熊繁 王颖 黎诗祷 田曼 郑翠红 黄光英 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Functional constipation （FC） is a common functional bowel disorder disease that affects life quality of a large number of people. This study aimed to explore the impact of different intensities of electro-acupuncture （EA） treatment for FC patients. Totally, 111 patients with FC meeting the Rome III criteria were randomly assigned to different intensities of EA groups （low and high intensity of EA groups） and medicine-controlled （MC） group. In EA groups, patients were treated with EA at quchi （Llll） and shangjuxu （ST37） bilaterally for 4 weeks, 5 times/week in the first 2 weeks, and 3 times/week in the last 2 weeks. In MC group, 5 mg mosapride citrate was administered orally 3 times/day for 4 weeks. Spontaneous bowel movement frequency each day was recorded using a consti- pation diary. Self-rating anxiety scale （SAS） and self-rating depression scale （SDS） were used to assess the patients＇ psychological state. Cortisol （CORT）, substance P （SP）, and vasoactive intestinal polypep- tide （VIP） were evaluated at baseline and at the end of 4 weeks after treatment. As compared with the baseline, there was statistically significant increase in stool frequency every week （P〈0.01）, but there was no statistically significant difference among the three groups. As compared with the baseline, after 4 weeks of EA therapy, the scores of SDS and serum levels of CORT were decreased significantly in low intensity of EA group （P〈0.01）, and the serum levels of SP and VIP were increased significantly （P〈0.05）; the scores of SAS and SDS and serum levels of CORT were decreased significantly in high intensity of EA group （P〈0.05）, and the serum levels of SP and VIP were increased significantly （P〈0.05）; the serum levels of CORT and VIP were increased significantly in MC group （P〈0.05）. As compared with MC group, after 4 weeks of treatment, the serum levels of SP were signifcicantly in- creased in low intensity of EA group （P〈0.01）. Low and high intensities of EA could increase the stool frequency, improve the FC patient＇s anxiety and depression, reduce the serum levels of CORT, and in- crease the serum levels of SP and VIP effectively. It is concluded that both low and high intensities of EA are effective for FC patients, but there is no significant difference between the low and high intensi- ties of EA.